Circulating and Tumor-Infiltrating NK Cells From Clear Cell Renal Cell Carcinoma Patients Exhibit a Predominantly Inhibitory Phenotype Characterized by Overexpression of CD85j, CD45, CD48 and PD-1 - Ziblat, Andrea; Iraolagoitia, Ximena Lucía Raffo; Nuñez, Sol Yanel; Torres, Nicolás Ignacio; Secchiari, Florencia; Sierra, Jessica Mariel; Spallanzani, Raúl Germán; Rovegno, Agustín; Secin, Fernando Pablo; Fuertes, Mercedes Beatriz; Domaica, Carolina Inés; Zwirner, Norberto Walter (Frontiers in Immunology, 2021)
Although natural killer (NK) cells infiltrate clear cell renal cell carcinomas (ccRCC), the most frequent malignancy of the kidney, tumor progression suggests that they become dysfunctional. As ccRCC-driven subversion of NK cell effector functions is usually accompanied by phenotypic changes, analysis of such alterations might lead to the identification of novel biomarkers and/or targets in immuno-oncology. Consequently, we performed a phenotypic analysis of peripheral blood NK cells (PBNK) and tumor-infiltrating NK cells (TINK) from ccRCC patients. Compared to HD, PBNK from ccRCC patients exhibited features of activated cells as shown by CD25, CD69 and CD62L expression. They also displayed increased expression of DNAM-1, CD48, CD45, MHC-I, reduced expression of NKG2D, and higher frequencies of CD85j+ and PD-1+ cells. In addition, compared to PBNK from ccRCC patients, TINK exhibited higher expression of activation markers, tissue residency features and decreased expression of the activating receptors DNAM-1, NKp30, NKp46, NKp80 and CD16, suggesting a more inhibitory phenotype. Analysis of The Cancer Genome Atlas (TCGA) revealed that CD48, CD45, CD85j and PD-1 are significantly overexpressed in ccRCC and that their expression is associated with an NK cell infiltration signature. Calculation of z-scores revealed that their expression on PBNK, alone or combined, distinguished ccRCC patients from HD. Therefore, these molecules emerge as novel potential biomarkers and our results suggest that they might constitute possible targets for immunotherapy in ccRCC patients.